Association of Maxillary Osteoma with Choroidal Osteoma - Najam-ul-Hasnain Khan, Muhammad Moin, Najam-ul-Hasnain Khan (Pakistan Journal of Ophthalmology, 2006)
Osteomas of the paranasl sinuses are common slowly growing lesions and often appear as asymptomatic finding on radiological examination. They represent the most common benign neoplasm of the nose and paranasal sinuses1,2. We report a case of a young male who had a maxillary osteoma extending into the orbit and a choroidal osteoma on the same side. This association of orbital and choroidal osteoma has not been reported before in literature.